The Response of Macrobenthic Communities to Environmental Variability in Tropical Coastal Waters - Tavakoly Sany, Seyedeh Belin; Tajfard, Mohammad; Hashim, Rosli; Rezayi, Majid; Rahman, Mohammad Azizur; Karlen, David J. (Springer Verlag, 2018)
The relative contributions of spatial and temporal fluctuations are different in shaping natural communities in a tropical coastal/estuarine system. Understanding how coastal communities respond to these fluctuations is still equivocal, and thus, available data are rare. Here, multiple analytical approaches were used to identify key spatial and temporal factors, and to quantify their relative roles in shaping a macrobenthic community through space (contamination degree, physical parameters, and sediment characteristics) and time (climatic factors, season, and year). A dataset of eight sampling times was analyzed over a period of 2 years, in which macrobenthic species abundances were sampled. A total of 33 species were identified, including 18 bivalves, 5 gastropods, and 4 crustaceans. The other taxa were less diverse. The results show that there were no significant temporal changes of macrobenthic community structure, but spatial changes were significant and synchronized with environmental factors (i.e., sediment characteristics, water depth, and the distance from anthropogenic sources). This study demonstrates that spatial factors played a primary role in structuring of macrobenthic assemblages, whereas the influence of temporal factors appeared less across geographically distinct sites. Thus, temporal variation of a coastal macrobenthic community appears to be controlled by partly different processes at different scales.